2011
DOI: 10.1111/j.1745-4514.2011.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antimicrobial Activities of Different Extracts of Some Medicinal Herbs Consumed as Tea and Spices in Turkey

Abstract: Methanol (MeOH) extracts, infusions and decoctions of eight plants were investigated for their antioxidant activity using phosphomolybdenum and 2,2‐diphenyl‐1‐picrylhydrazyl assays: Cassia angustifolia (Senna tea), Foeniculum vulgare (fennel), Pimpinella anisum (anise), Laurus nobilis (laurel), Tilia vulgaris (linden tea), Urtica dioica (nettle), Petroselinum crispum (parsley) and Anethum graveolens (dill). The results showed that the highest antioxidant activity was found in MeOH extract of linden. Linden MeO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 21 publications
(35 reference statements)
4
31
0
1
Order By: Relevance
“…The results reported for radical scavenging activity of fennel extracts (36.84% at the dose of 2 mg/mL) are similar to our results (Albayrak et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…The results reported for radical scavenging activity of fennel extracts (36.84% at the dose of 2 mg/mL) are similar to our results (Albayrak et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…14 -17 Similarly, there are a number of reports on the phenolic content of anise in the seeds, 1,18 fruits, leaves, 19 roots 13 and whole plant. 10 The antioxidant activity and essential oil content of plants may vary considerably with respect to environmental conditions, nutrient and water accessibility and genetic potential of the crop. 20,21 Among nutrients, zinc (Zn) is one the most important basic micronutrients and has a specific physiological function within plants, being required in membrane integrity, 22 carbohydrate metabolism, 23 indole-3-acetic acid (IAA) biosynthesis and transport, 24,25 control mechanisms of generation and detoxification of oxygen-derived radicals and activation of various antioxidant enzymes, 26 -29 protein synthesis and RNA metabolism 30,31 and photosynthesis.…”
Section: -3mentioning
confidence: 99%
“…The essential oil of anise fruit also contains other major compounds such as estragol, anisaldehyde, γ ‐himachalene and cis ‐anethole . Several studies have reported the antioxidant activity of anise extracts obtained from the whole plant, seeds, roots and essential oil . Similarly, there are a number of reports on the phenolic content of anise in the seeds, fruits, leaves, roots and whole plant …”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory effects of several natural bioactive compounds from berries and grapes (Puupponen-Pimia et al, 2001;Zanoli & Zavatti, 2008) herbs and spices (Albayrak, Aksoy, Sagdic, & Albayrak, 2012;Shan et al, 2007b;Shan, Cai, Brooks, & Corke, 2007a) and other plant extracts (Pereira et al, 2007b;RaybaudiMassilia, Mosqueda-Melgar, Soliva-Fortuny, & Martin-Belloso, 2009;Santas et al, 2010) were tested against food-relevant bacteria including: E. coli, Salmonella, Listeria, and Staphylococcus. Although the antimicrobial activity of some PCs including: thymol (Lambert et al, 2001;Santas et al, 2010), eugenol (Phanthong, Lomarat, Chomnawangb, & Bunyapraphatsaraa, 2013), carvacrol (Lambert et al, 2001;Santas et al, 2010), quercetin (Yao et al, 2011) and myricetin (Puupponen-Pimia et al, 2001) has been previously reported, the response after the long term exposure was not reported and there are still many unexplored sources.…”
Section: Introductionmentioning
confidence: 99%